ROLE OF INSULIN RESISTANCE AND ITS CORRECTION IN THE PROCESS OF VASCULAR AGING - E. N. Dudinskaya; O. N. Tkacheva; I. D. Strazhesko; D. U. Akasheva (Столичная издательская компания, 2015)
Insulin resistance plays the main role in the pathogenesis of diabetes mellitus and its complications. It is also a major factor of the pathology associated with age, which leads to accelerated aging. Data about the role of insulin resistance and its correction in vascular aging are presented.